No me ames - Lopez, Jennifer; Anthony, Marc; Sony Music Entertainment (Santa Monica, California : Sony Music Entertainment, 1999)
Contains two tracks in Spanish taken from the album On The 6.
CD 1 : No Me Ames (duet with Marc Anthony) -- No Me Ames (tropical remix).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, English; Songs, Spanish